Alternative selection rules for one- and two-photon transitions in tribenzotetraazachlorin: Quasi-centrosymmetrical π-conjugation pathway of formally non-centrosymmetrical molecule - Makarov, Nikolay S. (AIP Publishing LLC, 2013)
We compare the two-photon absorption (2PA) spectra of non-centrosymmetrical metal-free tribenzo-tetraazachlorin (H(2)TBTAC) and analogous symmetrical tetra-tert-butyl-phthalocyanine (H(2)TtBuPc). Surprisingly, despite formal lack of center of inversion, the 2PA spectrum of H(2)TBTAC displays a two-photon allowed transition at 935 nm, similar to gerade–gerade (g–g) transitions observed in H(2)TtBuPc and in other symmetrical phthalocyanines. This transition is even better resolved in the singlet–singlet excited-state absorption spectrum. We tentatively explain the survival of the g–g transition in H(2)TBTAC by assuming that the main π-electron conjugation pathway in the tetraaza-substituted tetrapyrrole macrocycle bypasses the outer parts of the two oppositely located isoindole rings and thus renders the optically responsive core of the chromophore quasi-centrosymmetrical. By using the independently measured ground- and excited-state absorption extinction coefficients, we also show that the two-photon absorptivity can be quantitatively explained by a simple three-level model with the lowest energy Q(1) state serving as an intermediate level.